Investigation of cutaneous photoadaptation to narrowband ultraviolet B. (18th February 2014) - Darné, S.; Stewart, L.C.; Farr, P.M.; Hampton, P.J.
Summary: Background: Photoadaptation describes the skin's ability to withstand an increased dose of ultraviolet (UV) radiation with repeated exposure, and this is the reason for exposure doses being increased during a course of phototherapy. However, directly measured data on photoadaptation are available only for broadband (BB) and not narrowband (NB)‐UVB. Objectives: To measure photoadaptation to narrowband UVB. Methods: We measured the degree of photoadaptation in patients with psoriasis during a standard course of NB‐UVB phototherapy. The minimal erythemal dose (MED) was measured before and towards the end of a course of phototherapy. An adaptation factor (AF) was calculated for each patient using the ratio of final MED to initial MED. Sigmoid dose–response curves were also constructed. Results: MED results were available for 50 patients (mean age 44 years, 28 female). The mean AF was 2·7 (95% confidence interval 2·4–3·0). There was no significant correlation between AF and skin type or initial MED. Dose–response curves were right shifted and parallel after phototherapy, and there was no significant difference in the maximum slope ( P  = 0·73). Conclusions: The photoadaptation caused by NB‐UVB is considerably less than that reported for BB‐UVB. The variation in photoadaptation between patients was not explained by skin type or baseline MED. Physical factors (such as tanning and epidermal thickening) are probably sufficient to account for photoadaptation, rather than downregulation of the inflammatory response. These data should help in the design of phototherapy protocols for NB‐UVB to achieve optimal clearance of psoriasis. Abstract : What's already known about this topic? Skin is able to withstand increasing doses of ultraviolet (UV) radiation with repeated exposure (photoadaptation), hence the dose increments in phototherapy protocols. Photoadaptation is mediated by tanning, epidermal thickening and possibly changes in the inflammatory response. Photoadaptation to broadband UVB has been studied, but there is only a single retrospective review on photoadaptation to narrowband UVB. What does this study add? Photoadaptation to narrowband UVB is much less than to broadband UVB. Patients with psoriasis tolerate, on average, 2·7 times the dose of UV radiation at the end of phototherapy compared with their first exposure. This is the first step towards calculating accurate phototherapy dosing increments for narrowband UVB. Dose–response curves suggest that photoadaptation is mediated by physical mechanisms such as epidermal thickening or tanning, rather than downregulation of the inflammatory response.